2014
DOI: 10.1093/jisesa/ieu106
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition Deterrent Activities of Pachyrhizus erosus Seed Extract and Other Natural Products on Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: An extract of a rotenone-containing plant yam bean, Pachyrhizus erosus (L.) Urban, seeds was tested against the diamondback moth, Plutella xylostella (L.) in a greenhouse to determine its potential as an oviposition deterrent and compared with coumarin and rutin, known as diamondback moth oviposition deterrent compounds, rotenone, and an extract of Peruvian cube root, at a concentration of 0.5% (w/v). Oviposition deterrent index (ODI) was used to determine effects of extracts or compounds in inhibiting oviposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The use of botanical pesticides could present a safe alternative compared to the use of broad spectrum chemical insecticides in crop protection [12, 13]. In nature, plants produce secondary metabolites during their interaction with insects and these metabolites can act as toxicants [14], antifeedants [15], anti-oviposition agents and deterrents towards insects [16]. Because of such wide insecticidal properties, the study of secondary metabolites and the development of new potent formulations based on them have become increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…The use of botanical pesticides could present a safe alternative compared to the use of broad spectrum chemical insecticides in crop protection [12, 13]. In nature, plants produce secondary metabolites during their interaction with insects and these metabolites can act as toxicants [14], antifeedants [15], anti-oviposition agents and deterrents towards insects [16]. Because of such wide insecticidal properties, the study of secondary metabolites and the development of new potent formulations based on them have become increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al (2003) reported the mean egg laying by P. xylostella decreased from 56.7 to 32.66 on plant surface treated with A. calamus (aqueous extract) as the time increased from 0 to 3 days. Similarly, Basukriadi and Wilkins (2014) also reported the residual effect of yam been seed extract (1%) as egg laying decreased from 1 to 3 days from 77 to 59 of P. xylostella. Plant extracts having nonvolatile properties are more useful compounds for oviposition deterrent (Renwick, 1988).…”
Section: Residual Activitymentioning
confidence: 81%
“…The advantage of this is its selective action against parasites and pest predators, as well as pollinators. Plant antifeedant substances prepared from secondary metabolites are found in all groups; however, the most effective insect feeding inhibitors come from terpenoids, alkaloids, saponins, and polyphenols (Koul, 2005) and oviposition reducers come from cumarina and rutina (Tabashnik, 1985) andrographolide (Hermawan et al, 1998) and a-terpineno, Limonene, linalool (Zhang et al, 2004), essential oils (Dover, 1985;Zhang et al, 2004) and plant extracts (Abbasipour et al, 2010;Basukriadi & Wilkins, 2014;Chen et al, 1996;Egigu et al, 2010;Kodjo et al, 2011;Patil et al, 2003). These substances also inhibit the oviposition of P. xylostella.…”
Section: Introductionmentioning
confidence: 99%